Sustainable development through global circular economy practices - Maguire, Stuart; Robson, Ian (Emerald Publishing Limited, 2023)
The battle to preserve the environment is only just beginning - organisations and governments cannot underestimate the public outcry for cleaner environments and an end to increases in global warming. The Circular Economy has been able to tap into the current zeitgeist and is being coveted by many academic disciplines. Offering a detailed overview of what is required to move towards a circular economy by providing a series of cases alongside each chapter that illustrate practice in relation to theory, Maguire and Robson deliver a lens through which academics and students can explore what is emerging as state of the art. The chapters contain a critical and balanced treatment of theory and practice on the subjects of sustainable development and the circular economy, setting out and evaluating the theoretical landscape alongside a grand narrative drawn from systems thinking and the environmental, social, and governance paradigms. For students, academics and practitioners, Sustainable Development Through Global Circular Economy Practices is a go-to book with original insights from a theoretical perspective about how the global economy integrates, and how this integration can be leveraged to move practice toward sustainable practice.